Exploring Sixth Graders' Interest in English Language Learning : A Descriptive Study in Ngabang - Aswan Aswan; Aunurrahman Aunurrahman; Maliqul Hafis (CV. AFDIFAL MAJU BERKAH, 2026)
This study aimed to investigate the level of students' interest in learning English at a public primary school in Ngabang in the academic year 2025/2026. This research employed a quantitative descriptive survey design. The population of this study consisted of sixth-grade students. The sample was selected using a total sampling technique, involving all students as participants. The instrument used in this study was a closed-ended questionnaire consisting of 14 items. After conducting a pilot test, two items were found to be invalid and excluded. This resulted in 12 valid items used in the main data collection. The data were analyzed using descriptive statistics, including mean scores and percentages. The findings showed that the overall mean score of students' interest was 3.44, which was categorized as